Ernest Bozzano: An Italian Spiritualist and Psychical Researcher - Gasperini, Luca (Journal of Scientific Exploration, 2011)
Ernesto Bozzano (1862-1943) was a luminary in psychical and spiritualistic studies in Italy, to which he contributed numerous publications which were also distributed abroad; he was a supporter of human survival. Forgotten for a long time despite the role he played until the 1940s, this article, after a brief look at the studies dedicated to him, furnishes a profile of the life and thinking of Bozzano, paying particular attention to the events that brought him to the eyes of the international community of psychical researchers.